2013
DOI: 10.1038/ncomms2814
|View full text |Cite
|
Sign up to set email alerts
|

The genomics of selection in dogs and the parallel evolution between dogs and humans

Abstract: The genetic bases of demographic changes and artificial selection underlying domestication are of great interest in evolutionary biology. Here we perform whole-genome sequencing of multiple grey wolves, Chinese indigenous dogs and dogs of diverse breeds. Demographic analysis show that the split between wolves and Chinese indigenous dogs occurred 32,000 years ago and that the subsequent bottlenecks were mild. Therefore, dogs may have been under human selection over a much longer time than previously concluded, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
259
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(292 citation statements)
references
References 57 publications
17
259
1
5
Order By: Relevance
“…These results can provide the support for a genetic role in human-animal interaction. Wang et al (2013) insisted parallel selection in humans and dogs, and our results could be considered in line with that conclusion. (b) Subtest Touch Sensitivity (TS) and Stability (S) were significantly different between ages.…”
Section: Discussionsupporting
confidence: 80%
“…These results can provide the support for a genetic role in human-animal interaction. Wang et al (2013) insisted parallel selection in humans and dogs, and our results could be considered in line with that conclusion. (b) Subtest Touch Sensitivity (TS) and Stability (S) were significantly different between ages.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is not a surprise and is consistent with the rapid evolution of genes in the nervous systems of other domestic animals, which has collectively been attributable to behavioral shifts that accompany domestication [14][15][16][17][18]. In addition, functional enrichment analysis of genes in regions with the top 1% XP-EHH scores revealed that many candidate genes related to the npg www.cell-research.com | Cell Research nervous system were over-represented in the following Human Phenotype Ontology (HPO) categories: abnormality of the nervous system (31 genes), abnormality of the central nervous system (30 genes), and cognitive impairment (25 genes) (P < 0.05) (Supplementary information, Table S8).…”
Section: Positively Selected Genes In Domestic Chickens Compared Withsupporting
confidence: 68%
“…Dogs also harbor weaker visual acuity compared to their wild ancestors, however, in contrast to chickens, there was no evidence for positive selection in visionrelated genes in previous studies [14][15][16]. Vision is important in birds for survival [58], but other sensory abilities including hearing and smell, might play more important roles in mammals.…”
Section: Discussionmentioning
confidence: 90%
“…El perro doméstico ha acompañado al hombre desde hace 33 mil años (1) , y desde entonces los procesos de domesticación y coevolución (2) han llevado a la casi indefectible presencia de perros en cualquier área donde se asiente un grupo humano. Estas poblaciones de perros cargan sus propios patógenos, entre los que se encuentran aquellos adaptados para transmitirse a los humanos y que se les denomina agentes zoonóticos (3) .…”
Section: Introductionunclassified